Discovery of CA9–005 as a new carbonic anhydrase 9 inhibitor using a DNA encoded-libraries - Ju Ho Lee; Sung Bum Park; Byumseok Koh; Jiwoo Kim; Kyoung Jin Choi; Jeonghui Im; Byungho Lim; Daesoo Kim; Byungwook Lee; Sunjong Yu; Nam-Chul Cho; Doyoun Kim; et al. (Results in Chemistry)
This study utilized DNA-encoded library (DEL) screening to identify novel inhibitors of carbonic anhydrase 9 (CA9), a key cancer target. Among the identified compounds, CA9–005 exhibited inhibitory activity and reduced cancer cell viability. Biolayer interferometry confirmed CA9–005's direct interaction with CA9, supported by structural modeling. These findings highlight the potential of DEL screening for drug discovery and establish CA9–005 as a anticancer candidate, warranting further structural and therapeutic optimization.